2017
DOI: 10.1542/hpeds.2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Training Faculty and Resident Perceptions on Teaching High-Value, Cost-Conscious Care: A Multi-Institutional Study

Abstract: Residents and faculty agree that HVCCC is important and that training institutions have a responsibility to address it. However, most residents were not comfortable with HVCCC. Faculty development in HVCCC as well as hospital support for access to pricing data will be key for programs to develop effective resident training in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Dutch residents, much like residents in other countries, are challenged to provide high-value care and take the costs into account. 18,33 Answering the first research question, we found that residents' learning was driven by their personal beliefs regarding HV3C, which led to equally different responses to HV3C-related dilemmas in clinical practice. When designing curricula, it is important to acknowledge different beliefs of residents and how these beliefs influence their HV3C learning.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dutch residents, much like residents in other countries, are challenged to provide high-value care and take the costs into account. 18,33 Answering the first research question, we found that residents' learning was driven by their personal beliefs regarding HV3C, which led to equally different responses to HV3C-related dilemmas in clinical practice. When designing curricula, it is important to acknowledge different beliefs of residents and how these beliefs influence their HV3C learning.…”
Section: Discussionmentioning
confidence: 95%
“…Role modeling HV3C is known to be scarce in residency training, due to lack of personal knowledge and training. 18 Specific training may be required, teaching physicians to become effective role models of HV3C. It is not surprising that today's academic faculty experience difficulties in teaching HV3C delivery, considering that they themselves were not trained in these competencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 36 The finding that residents value the inclusion of VBHC in educational plans positively confirms that they consider it an important topic that should be part of postgraduate medical education. 7 However, VBHC as a precondition for audits is not preferred. This might perhaps be due to the assumption that the inclusion in educational plans is less strict and binding compared to the theme being a precondition in postgraduate medical education quality assurance and audit procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Residents acknowledge the importance of VBHC and think that training institutions are responsible to address this topic. 7 Some of the leading national physician associations, such as The American College of Physicians and the American Board of Internal Medicine, share this view, resulting in the development of curricula that promote VBHC. 1 8– 10 Additionally, incorporating VBHC in postgraduate medical education has shown to be effective regarding training and stimulating non-medical (CanMEDs) competencies, thereby positively affecting the development of skills as medical expert, leader, communicator and collaborator.…”
Section: Introductionmentioning
confidence: 99%